Bioaccumulation and Concentration of Mercury in Rivers and Streams of the Hudson Bay Lowland - Warnock, Ashley (Scholarship@Western, 2015)
Methylmercury (MeHg) is a neurotoxin that biomagnifies in northern aquatic food webs to high enough concentrations to cause concern for human consumption. The Hudson Bay Lowland of Canada is projected to experience climate and land-use impact in the immediate future, and these environmental stressors may affect the exposure to and subsequent bioaccumulation of MeHg in subarctic fish populations. The focus of this research is to evaluate the spatial variability in total and MeHg in water, sediment, and biota within and across a range of subarctic streams and river reaches of the Hudson Bay Lowland. This data was then used to project potential bioaccumulation in subarctic riverine food webs. Across all study sites, MeHg in surface water was low, with a mean concentration of 0.087 ± 0.012 ng/L. Water MeHg was strongly positively correlated to sediment MeHg (R2 = 0.80), and both water and sediment contained a high proportion of total mercury as MeHg. Some individual small-bodied fish mercury concentrations were found to be above Canadian subsistence and commercial sale guidelines. The highest mean concentrations of fish mercury were 361.6 μg/kg and 156.7 μg/kg found at the two sampling sites corresponding to those with the highest water and sediment MeHg concentrations. Furthermore, calculation of MeHg bioaccumulation factors (BAFs) suggests that MeHg transfers predictably and highly efficiently in this subarctic food web. Using BAFs to predict changes to MeHg in fish with potential future changes to MeHg in surface waters demonstrates that small changes in Hg at the bottom of a food web can have large implications for fish tissue Hg.